Cholecystohepatic Duct: A Biliary Duct Variant Resulting in Postcholecystectomy Bile Leak—Case Report and Review of Normal and Common Variant Biliary Anatomy. (17th June 2019) - Meyer, Nathan; Al-Katib, Sayf; Sokhandon, Farnoosh
Abstract : Although relatively infrequent, bile duct leaks are among the primary complications of hepatobiliary surgery and cholecystectomy given the large number of these operations performed annually around the world. Variant biliary anatomy increases the risk of surgical complications, especially if unrecognized on preoperative imaging or intraoperatively. Presented here is a case of a patient with an unrecognized cholecystohepatic duct at the time of surgery leading to bile leak after cholecystectomy. Numerous factors made for a technically difficult surgery with obscuration of the true anatomy, ultimately resulting in transection of the cholecystohepatic duct. Understanding normal and variant biliary anatomy will help prevent avoidable complications of hepatobiliary surgery.